Factors Influencing Patient Satisfaction with Nursing Services in the Private Inpatient Health - Wahyuni, Sri; Widodo, Arif; Yulian, Vinami (Poltekkes Kemenkes Surakarta, 2024)
Background: Quality health services are every patient's hope, and understanding the factors that influence patient satisfaction with health services at private hospitals in Surakarta is important to improve the patient experience and overall quality of care. This research will provide valuable insights for hospital management and nursing staff in designing more effective interventions to improve services provided and patient satisfaction. This study aims to determine the factors that influence patient satisfaction with nursing services in inpatient rooms at private hospitals in Surakarta. Method: This research uses a quantitative approach with a cross-sectional design. The research sample consisted of 90 patients treated in inpatient wards who met the specified inclusion criteria. Data was collected using a structured questionnaire that measures the quality of nursing services and patient satisfaction. Data analysis was carried out using the multiple linear regression method to determine the influence of each variable on overall patient satisfaction. Results: Hospital nursing services in Surakarta have a significant effect on patient satisfaction with p<0.05, from the five dimensions, namely reliability, physical evidence, empathy, responsiveness, and assurance. All sizes have a significant effect (p<0.05) on the level of satisfaction. This occurs when patients have a good (fairly good) perception of hospital nursing services in Surakarta. Conclusion: The five dimensions of hospital nursing services in Surakarta, consisting of reliability, concrete evidence, empathy, responsiveness, and assurance, have a major impact on patient satisfaction in hospitals in Surakarta. Thus, it follows that patient satisfaction can be raised by hospitals providing high-quality nursing care.